2009
DOI: 10.1227/01.neu.0000346266.69493.88
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Supraorbital Approach Applied to Olfactory Groove Meningiomas

Abstract: The lateral supraorbital approach can be used safely for olfactory groove meningiomas of all sizes with no mortality and relatively low morbidity. Surgical results and tumor recurrence with this fast and simple approach are similar to those obtained with more extensive, complex, and time-consuming approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
118
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(133 citation statements)
references
References 64 publications
(68 reference statements)
7
118
1
3
Order By: Relevance
“…Several authors have reported complete resection rates of ≥ 90%, but only by including both Simpson Grade I and II, or without association of the degree of resection with the Simpson grading system. 31,35,39,42 As expected, authors who define GTR as Simpson Grade I only have reported lower GTR rates, ranging from 23.8% to 84.6%. 1,4,22 We use the same strict definition of GTR as Simpson Grade I only, and we also confirm the lack of residual meningioma in every case with postoperative MRI, which is critical for objective evaluation of resection.…”
Section: Surgical Outcomesupporting
confidence: 64%
See 4 more Smart Citations
“…Several authors have reported complete resection rates of ≥ 90%, but only by including both Simpson Grade I and II, or without association of the degree of resection with the Simpson grading system. 31,35,39,42 As expected, authors who define GTR as Simpson Grade I only have reported lower GTR rates, ranging from 23.8% to 84.6%. 1,4,22 We use the same strict definition of GTR as Simpson Grade I only, and we also confirm the lack of residual meningioma in every case with postoperative MRI, which is critical for objective evaluation of resection.…”
Section: Surgical Outcomesupporting
confidence: 64%
“…6,21,22,31,41 However, there are reports that tumor size is not correlated with residual lesion. 35 With the endoscopic experience, Simpson Grade I resection can be achieved in 90.5% of olfactory groove meningiomas ≤ 40 mm, but only in 45.8% of tumors > 40 mm.…”
Section: Surgical Outcomementioning
confidence: 99%
See 3 more Smart Citations